2012
DOI: 10.3399/bjgp12x630070
|View full text |Cite
|
Sign up to set email alerts
|

Service users' views of moving on from early intervention services for psychosis: a longitudinal qualitative study in primary care

Abstract: BackgroundThe role of primary care for young people with psychosis, and transitions between specialist mental health services and primary care, are underexplored areas, both clinically and in research terms. AimTo explore service users' perspectives of early intervention services and primary care, in-depth and over time. Design and settingLongitudinal qualitative methodology in five geographically diverse sites across England. MethodSemi-structured interviews with 21 young people with first-episode psychosis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
92
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(95 citation statements)
references
References 18 publications
3
92
0
Order By: Relevance
“…Furthermore, service users may still be expecting primary care to provide more of the support required. For instance, a recent study on psychosis early intervention services for young people has shown that service users expect GPs to advocate for and navigate the health system 39. Indeed, one could argue for a more bottom-up framework for guiding, supporting and helping primary care workers to make clinical decisions and maintain a more active and open care pathway process.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, service users may still be expecting primary care to provide more of the support required. For instance, a recent study on psychosis early intervention services for young people has shown that service users expect GPs to advocate for and navigate the health system 39. Indeed, one could argue for a more bottom-up framework for guiding, supporting and helping primary care workers to make clinical decisions and maintain a more active and open care pathway process.…”
Section: Discussionmentioning
confidence: 99%
“…Although some have argued against allocating resources to EIP teams, there is evidence to support their effectiveness, particularly during their engagement in an individual's treatment (Marshall 2011). Patient satisfaction with the EIP approach is also high (Lester 2011 More research is needed to determine the most effective ingredients of the EIP approach. It seems likely that one of the most important components is active engagement.…”
Section: Early Intervention In Psychosis Teamsmentioning
confidence: 93%
“…The emerging sense of an adult self and identity will be disrupted by the arrival of mental illness. This change in identity was explored in the study published by EDEN group mentioned earlier (Lester 2011). The young participants highlighted their experiences of a changed sense of self and of perceived stigma.…”
Section: Adolescent Identity and Relationships With Professionalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, there is evidence that every pound or dollar spent on EIS leads to exponential downstream cost savings; these are associated with fewer future inpatient admissions, lower future treatment costs for mental and physical health problems, and indirect savings associated with people remaining in or entering employment (Mihalopoulos et al 2009;McCrone et al 2011). Finally, EIS are seen as largely beneficial by the patients themselves and their carers (Lester et al 2011(Lester et al , 2012.…”
Section: Development and Controversies Of Early Intervention In Psychmentioning
confidence: 99%